The Influence Of Debt Policy, Tax Avoidance, And Sales Growth On Firm Value In Food And Beverage Sub-Sector Companies Listed On The Indonesia Stock Exchange In 2022-2024 - Maimunah, Siti; Fauzan Fuadi, Andi Mulyono, Fitria Fertha Agustina, (Jurnal Mirai Management, 2025)
Firm value not only reflects the current intrinsic value, but also indicates the prospects and expectations of the company’s ability to enhance its value in the future. Stock price fluctuations among several companies in the food and beverage sub-sector during the 2022–2024 period show significant changes, which affect corporate performance and may influence market perceptions of firm value. This study examines the influence of debt policy, tax avoidance, and sales growth on firm value using a quantitative approach and multiple linear regression analysis. The sample was selected using purposive sampling from a population of 26 companies, resulting in 19 companies that met the criteria. With a three-year observation period, a total of 57 data points were obtained. The study finds that debt policy has a negative and significant effect on firm value. Tax avoidance has a positive and significant effect on firm value. Sales growth also has a positive and significant effect on firm value. These findings support the signaling theory, which suggests that every piece of financial information from a company serves as a signal positive (good news) or negative (bad news) and these signals influence the rise or fall of a firm value. The results of this study emphasize the importance of effective corporate financial strategies in achieving the desired firm value and overall corporate objectives.